Master of public health) MPH( Modular Need Analysis Course with Management Orientation and Health System Reforms for the Talented Students - Athar Omid; Mahsa Gharezi; Nikoo Yammani; Mohammadreza rezayatmand; Pejman Aghdak; Azita Rostami; Mojgan Akbarzadeh (مجله ایرانی آموزش در علوم پزشکی, 2020)
Introduction: The Master of Public Health (MPH) course in the Iranian health system is known as the training course for managers. The MPH course, is mainly used to empower students in the managerial and analytical skills of the community health system. The this study endeavored to to analyze the needs of the MPH course to launch a course for talented general medical students at Isfahan University of Medical Sciences. Methods: This need analysis study was conducted through the modified Delphi technique. Initially, the literature was reviewed. During the search phase, curricula of this course were extracted from national (Hamedan, Shiraz, Shahid Beheshti and Tehran) and international (Arizona and Miami) universities where the MPH management course is offered. The results of literatures review were summarized in the focus group session and developed as a questionnaire. The questionnaire was distributed among 25 general practitioners and the gathered data were analyzed through descriptive statistics (frequency). Results: The results of the literature review were described and a questionnaire was developed by forming a three-focus-group session. The results of the distribution of the questionnaire among 25 general practitioners and the analysis of its data were like this: Disaster management, crisis management, maternal health, children, the elderly, nutrition and addiction, social determinants of health, community health management, population and aging, health education and health promotion, environmental health education, school health, occupational health and statistics and research methods Conclusion: The results revealed that the selected topics except the dissertation are of importance for more than 70% of the samples.